Yeast Systems Biology: Our Best Shot at Modeling a Cell. Issue 2 (1st October 2014) - Boone, Charles
Abstract: THE Genetics Society of America's Edward Novitski Prize recognizes an extraordinary level of creativity and intellectual ingenuity in the solution of significant problems in genetics research. The 2014 recipient, Charles Boone, has risen to the top of the emergent discipline of postgenome systems biology by focusing on the global mapping of genetic interaction networks. Boone invented the synthetic genetic array (SGA) technology, which provides an automated method to cross thousands of strains carrying precise mutations and map large-scale yeast genetic interactions. These network maps offer researchers a functional wiring diagram of the cell, which clusters genes into specific pathways and reveals functional connections.